Taking Orlistat: Predicting Weight Loss over 6 Months - Amelia Hollywood; Jane Ogden (Journal of Obesity)
This study explored the predictors of weight loss following orlistat with a focus on both baseline variables and changes in beliefs and behaviours occurring over the course of taking the drug. Patients (n=566) prescribed orlistat completed a questionnaire at baseline and after 6 months concerning their weight, beliefs and behaviours. By 6 months the majority had lost some weight and showed improvements in diet. Many had also stopped taking the drug and a large minority reported using it flexibly as a lifestyle drug. Those who lost most weight showed a decrease in beliefs in a medical solution, a decrease in unhealthy eating, an increased belief in treatment control and an increased belief that the unpleasant consequences are both due to their eating behaviour and just part of the drug. When taken with fatty food orlistat causes symptoms such as anal leakage and oily stools. These may encourage some patients to focus on the behavioural aspects of their weight problem thus promoting the dietary changes needed for both short and longer term weight loss. When prescribing orlistat, clinicians should encourage patients to see the consequences as an education as a means to promote the effectiveness of this form of medical management.